1977
DOI: 10.1111/j.1559-1816.1977.tb02414.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences, Situational Constraints, and Police Shooting Incidents

Abstract: Differences in the personal nature of police officers as well as differences among the situational constraints due to assignments are considered in an examination of the occurrences of police involvement in shooting incidents. The Poisson and negative binomial models used in accident research are considered for representing the occurrence of shooting incidents. Data were gathered from incidents in a large metropolitan police department over a 34‐month period and used to test the two models. Various analyses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Analyzing 7 years of shooting data from the Kansas City, Missouri Police Department, Sherman and Blumberg (1981) found that officer education appeared to have no significant effect on discharging firearms when controlling for assignment, age, and length of service. 5 Four years earlier, Inn and Wheeler (1977) produced similar results, finding that college education did not cause significant differences in shooting incidents among officers. In addition, Hayden (1981) found that individual officer characteristics, including education, did not predict the decision to use deadly force.…”
Section: The Effect Of Officer Education On the Use Of Forcementioning
confidence: 78%
“…Analyzing 7 years of shooting data from the Kansas City, Missouri Police Department, Sherman and Blumberg (1981) found that officer education appeared to have no significant effect on discharging firearms when controlling for assignment, age, and length of service. 5 Four years earlier, Inn and Wheeler (1977) produced similar results, finding that college education did not cause significant differences in shooting incidents among officers. In addition, Hayden (1981) found that individual officer characteristics, including education, did not predict the decision to use deadly force.…”
Section: The Effect Of Officer Education On the Use Of Forcementioning
confidence: 78%